2020
DOI: 10.1080/23723556.2020.1715766
|View full text |Cite
|
Sign up to set email alerts
|

CD36: a key mediator of resistance to HER2 inhibitors in breast cancer

Abstract: Acquired resistance to anti-HER2 therapy is a significant clinical challenge in breast cancer. We recently discovered that during acquisition of resistance to HER2 inhibition, upregulation of the fatty acid transporter CD36 takes place, playing a key role in metabolic rewiring and resistance to anti-HER2 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
0
15
1
Order By: Relevance
“…These data demonstrate that trastuzumab administration in patients with breast cancer, a treatment according to one report associated with a 34% rate of brain metastasis 5 , results in increased expression of a cell surface marker that we have observed to be a defining transcriptional feature of early-onset breast cancer 6 , a marker whose expression has been associated with enhanced metastasis in mouse models of cancer 7 , and that this increased expression is likely a direct result of treatment with trastuzumab 3 . Though it has been argued that CD36 is up-regulated during acquisition of resistance in response to HER2 inhibition by trastuzumab 8 , we find here that CD36 up-regulation is readily observable in patient tumor following a single administration of trastuzumab, arguing this reflects primary transcriptional effects of trastuzumab as opposed to changes in gene expression observed over a course of treatment (tumor evolution).…”
Section: Discussioncontrasting
confidence: 51%
“…These data demonstrate that trastuzumab administration in patients with breast cancer, a treatment according to one report associated with a 34% rate of brain metastasis 5 , results in increased expression of a cell surface marker that we have observed to be a defining transcriptional feature of early-onset breast cancer 6 , a marker whose expression has been associated with enhanced metastasis in mouse models of cancer 7 , and that this increased expression is likely a direct result of treatment with trastuzumab 3 . Though it has been argued that CD36 is up-regulated during acquisition of resistance in response to HER2 inhibition by trastuzumab 8 , we find here that CD36 up-regulation is readily observable in patient tumor following a single administration of trastuzumab, arguing this reflects primary transcriptional effects of trastuzumab as opposed to changes in gene expression observed over a course of treatment (tumor evolution).…”
Section: Discussioncontrasting
confidence: 51%
“…The present study found CD36 expression and its prognostic value in multiple cancer types. In addition, the expression of CD36 was significantly associated with current predictors for the efficacy of ICIs [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…Vazquez-Martin et al [ 110 ] reported that the FASN-mediated FAs de novo biosynthesis is inhibited in response to HER2 inhibition and cancer cells undergo apoptosis, indicating crosstalk between FASN and HER2. However, a recent study found that lapatinib-resistant cells are unresponsive to (-)-C75, which is well-established to suppress FASN [ 111 ] . Furthermore, the lapatinib-resistant cells showed a significantly higher level of CD36 with an enhanced rate of FAs uptake, as well as an increase in the presence of lipid droplets compared to their sensitive counterparts [ 112 ] .…”
Section: Specific Mechanisms Of Resistancementioning
confidence: 99%